Quartz crystallographic and morphologic fabrics during folding/transposition in mylonites - Hongn, Fernando Daniel (2001)
Quartz grain shape fabrics (GSF) and c-axis lattice preferred orientation (LPO) were investigated in folded quartz ribbons with variable fold geometry in low metamorphic-grade granitic mylonites from northwestern Argentina. The folds, which vary from open to isoclinal, show an asymmetric short limb–long limb geometry developed simultaneously with the quartz fabrics during progressive simple shear. GSF shows a consistent obliquity relative to the bulk shear plane throughout the folded ribbons. GSF inclination varies between 25° and 45° oblique to the shear plane, indicating that relatively small finite strain increments (γ∼1.2) are attained before the GSF regeneration. In contrast, the c-axis preferred orientation varies throughout the folded ribbons. Unfolded ribbons and long limbs of folds show a typical c-axis maximum near the shear plane pole, while short limbs of tight and isoclinal folds show a c-axis maximum nearly orthogonal to that of long limbs. This pattern of domainal LPO is maintained in thickened ribbons derived from folding and transposition. This indicates that the GSF regeneration is comparatively much faster than a cycle of folding/transposition. Conversely, the LPO regeneration is much slower. We conclude that folding/transposition is a mechanism for development of domainal quartz LPO in kinematic frameworks with dominant simple shear.